Pure pairs. X. Tournaments and the strong Erdos-Hajnal property - Chudnovsky, M; Scott, A; Seymour, P; Spirkl, S (Elsevier, 2023)
A pure pair in a tournament G is an ordered pair (A, B) of disjoint subsets of V (G) such that every vertex in B is adjacent from every vertex in A. Which tournaments H have the property that if G is a tournament not containing H as a subtournament, and |G| > 1, there is a pure pair (A, B) in G with |A|, |B| ≥ c|G|, where c > 0 is a constant independent of G? Let us say that such a tournament H has the strong EH-property As far as we know, it might be that a tournament H has this property if and only if its vertex set has a linear ordering in which its backedges form a forest. Certainly this condition is necessary, but we are far from proving sufficiency. We make a small step in this direction, showing that if a tournament can be ordered with at most three backedges then it has the strong EH-property (except for one case, that we could not decide). In particular, every tournament with at most six vertices has the property, except for three that we could not decide. We also give a seven-vertex tournament that does not have the strong EH-property. This is related to the Erd˝os-Hajnal conjecture, which in one form says that for every tournament H there exists τ > 0 such that every tournament G not containing H as a subtournament has a transitive subtournament of cardinality at least |G| τ . Let us say that a tournament H satisfying this has the EH-property. It is known that every tournament with the strong EH-property also has the EH-property; so our result extends work by Berger, Choromanski and Chudnovsky, who proved that every tournament with at most six vertices has the EH-property, except for one that they did not decide.